2021
DOI: 10.5606/tgkdc.dergisi.2021.21183
|View full text |Cite
|
Sign up to set email alerts
|

Funnel technique for wide infrarenal aneurysm neck with Lifetech Ankura™ Stent Graft System

Abstract: Background: In this study, we present our mid-term results in patients undergoing treatment with the funnel technique and describe technical issues for this bailout technique in extra-wide infrarenal necks. Methods: Between January 2018 and June 2020, a total of seven male, symptomatic patients (median: 74.5 years; range, 64 to 84 years) who had comorbidities and were in the American Society for Anesthesiologists Class IV and treated by the funnel technique in an endovascular fashion were included. Pre- and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…It provides an advantage in the application of assistive TEVAR techniques, especially in SMFSG. The wide spectrum of the thoracic endograft length also facilitates some other techniques like a funnel in wide infrarenal aortic necks with 60 mm in length [15]. Long-term follow-up of these patients will be more decisive in terms of the durability of the endografts and the success of the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…It provides an advantage in the application of assistive TEVAR techniques, especially in SMFSG. The wide spectrum of the thoracic endograft length also facilitates some other techniques like a funnel in wide infrarenal aortic necks with 60 mm in length [15]. Long-term follow-up of these patients will be more decisive in terms of the durability of the endografts and the success of the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it may be a result of endografts radial force. [23,24] Neck enlargement can be defined as dilatation of 3-mm or more between the first postoperative and last available CTA. The incidence of neck enlargement in all EVAR patients during two years of follow-up was 20%.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Other similar studies have also shown that pre-EVAR PIAND is not associated with post-EVAR proximal neck enlargement. [21][22][23][24][25] Diameter changes of the proximal neck after EVAR have been investigated in several studies which obtained varying results. Diehm et al [26] reported a >15% increase in proximal neck diameter in 24.9% of patients at two-year follow-up and in 35.1% of patients at four-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Fenestrated, branched endograft, chimney, or Surgeon Modified Fenestrated Stent Graft (SMFSG) place the proximal sealing side upwards to the abdominal visceral aorta or revascularizing the visceral branches with a parallel graft technique [ 6 ]. In such cases, as an endovascular solution, the so-called “Funnel” or “Trombone” technique may be used [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The Funnel technique is the hybrid assembly of a thoracic and abdominal aortic endograft, and is especially advantageous to the frail patient.…”
Section: Introductionmentioning
confidence: 99%
“…There are less than fifty cases reported [ 11 ], mostly case reports or case series [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], performed with aorto-uni-iliac or bifurcated abdominal endografts with a hybrid assembly of a 10 cm thoracic endograft. We started to perform this technique as a bail-out procedure in 2018, and after being confident about the outcomes [ 9 ], we began to perform them on patients with increased co-morbidities. We present one of the largest studies of Funnel-EVAR 60 mm Lifetech Ankura thoracic and abdominal bifurcated endograft.…”
Section: Introductionmentioning
confidence: 99%